From humans to canines: Unraveling the impact of metabolic health on mammary cancer across species - Osorio-Zambrano, William F; López-Valbuena, Fabián D; Montoya-Flórez, Luis M (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: The relationship between metabolic health and breast cancer has emerged as an expanding area of research in comparative oncology, particularly highlighted in studies conducted among humans and canines. Objective: This review explores how dietary habits, obesity, and metabolic syndromes influence the risk, progression, and response to breast cancer treatments. Methods: To this end, the impact of obesity, diet, and lifestyle on carcinogenesis mechanisms and prognosis in human and canine patients affected by mammary tumors was examined. Results: By examining comparative studies addressing the relationship between metabolic health and breast cancer in women and canines, common molecular and biochemical pathways in both species were identified. Conclusions: This approach provides a broader understanding of oncological diseases and their development, suggesting potential strategies for the prevention, diagnosis, and treatment of breast cancer from a metabolic perspective. However, as this area of research is still developing, it is necessary to explore new research lines to fully understand the complex relationship between metabolic health and cancer across different species from biochemical, molecular, genetic, and epigenetic perspectives. The goal is to gain valuable knowledge that contributes to the development of new diagnostic, prognostic, and therapeutic tools.